Social and conceptual background to the policy of reservation - Rai, Sheela (2002)
This article highlights the main theoretical arguments given by the proponents and opponents of the reservation policy in India and the US. In the current era of neo-capitalism and globalisation, both countries are struggling to balance their humanitarian responsibilities with the demands of greater decontrol and private initiative, which are integral to the market economy. This has an effect on their affirmative action programmes. - Reproduced.
Keywords: Backward classes